Induction of selective cytotoxicity and apoptosis in human T4 – lymphoblastoid cell line (CEMss) using boesenbergin a isolated from Boesenbergia rotunda L. - Ng, Kuan Beng (2013)
Boesenbergia rotunda (Roxb.) Schlecht (family zingiberaceae) is a rhizomatous herb that is distributed from north-eastern India to south-east Asia, especially in Indonesia, Thailand and Malaysia. Previous research has shown that the crude extract of this plant has cytotoxic properties. The current study examines the cytotoxic properties of boesenbergin A isolated from Boesenbergia rotunda. MTT assay was used to check the cytotoxicity of boesenbergin A. Boesenbergin A showed that it has the highest cytotoxicity towards human T4- lymphoblastoid cell line (CEMss)(IC50 = 8.11 μg/ml). The morphological assessment of apoptosis was monitored using normal and fluorescence microscopy. Evidence of apoptosis including blebbing and chromatin condensation was shown during the observation of microscopy analysis. The early and late phase of apoptosis was investigated using annexin V and DNA laddering assays, respectively. Annexin V assay revealed that early apoptosis is induced after treatment and DNA laddering confirmed that DNA fragmentation had occurred during late apoptosis. The mitochondrial membrane potential (MMP) was assessed by fluorescence microscopy and found that there is an increased in mitochondrial membrane potential in the treated CEMss cells. Human apoptosis proteome profiler assays were performed to investigate the mechanism of cell death. In addition, the protein levels of Bax, Bcl2 and Hsp 70 were also analyzed using western blot. Assays of caspase =-3/7, -8 and =-9 were carried out in order to test for induction during treatment. The activity of caspases -3/7, -8 and -9 was found to increase after treatment which indicates both intrinsic and extrinsic pathways are induced during apoptosis. Lastly, cell cycle progression was analyzed using flow cytometry and found that boesenbergin A is capable of inducing G2/M phase cell cycle arrest. The current findings warrant further research on boesenbergin A as a novel chemotherapeutic agent for leukemia intervention including studies in animal models.